Effect of shade on the emergence of seedlings of native timber species from the Yucatan Peninsula - Tzuc, Jaime Esteban Haas; Dzib Castillo, Benito Bernardo; Pool, Wilbert Santiago Poot; Médina, Ricardo Antonio Chiquini (Acta Universitaria, 2019)
The influence of solar radiation on the germination and emergence of seedlings has not been described for many of the timber species present in the tropics. The present research focuses on the emergence of native timber taxa seedlings of the Yucatan Peninsula under different degrees of shade (0%, 35%, 60% and 90%). For this, the evaluation of chakté (Caesalpinia mollis), jabín (Piscidia piscipula), and jujuché (Albizia tomentosa) was carried out. C. molli and A. tomentosa presented differences between treatments (p < 0.0001 and p < 0.01, respectively), both of which had the highest emergence of seedlings with the highest luminosity (0% of shade). The emergence time of the seedlings was four to five days, and the emergence of 100% was achieved in less days with 90% of shade for the three species.